DETERMINAN KECURANGAN AKADEMIK MAHASISWA AKUNTANSI DI MASA PANDEMI COVID-19 - Febrianti Kartika Ningrum; Evi Maria (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
This research aims to determine the determinants of academic fraud of accounting students during the Covid-19 pandemic using the fraud diamond dimension. The independent variables in this study are pressure, opportunity, rationalization and ability. Primary data collection is done through online surveys using questionnaire instruments through google form. The respondents obtained were as many as 161 accounting students, who were deleted as many as 27 accounting students and who were processed and analyzed as many as 134 accounting students. The results of this study showed that pressure and rationalization had a positive effect on academic fraud of accounting students during online learning, opportunities had no effect on academic cheating of accounting students during online learning and the ability to negatively affect the academic fraud of accounting students during online learning.